Cummins India : creating an inclusive workplace for women - Varkkey, Biju; Kulkarni, Vaibhavi (London : Indian Institute of Management, Ahmedabad, 2019)
The case describes Cummins India's journey of implementing large-scale change to bring about gender diversity and inclusion (D&I) in the organisation. With D&I listed as one of the five core values of the Cummins Corporation at the global level (the others being integrity, caring, excellence and teamwork), Cummins India began its journey to increase women's representation within the male-dominated manufacturing industry in 2004 and succeeded in significantly increasing the number of women in its corporate offices as well as its plants.
Originally Published InVarkkey, B., & Kulkarni, V. (2019). Cummins India: Creating an Inclusive Workplace for Women. IIMA/HRM0242. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Cummins, Inc -- Case studies; Women -- Employment -- India -- Case studies; Diversity in the workplace -- India -- Case studies; Internal combustion engine industry -- India -- Case studies; Electric generator industry -- India -- Case studies